Pontes de madeira para pequenos vãos para situações emergenciais - Novo, Carolina Montenegro [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
In Brazil there are many cases of cities that suffer from flooding. It often destroys much of the structure of the city, and isolates many families. Relying on emergency measures for these cases and similar cases is of utmost importance. This paper proposes the development of a project of a timber bridge that can be used in emergency situations such as occurs in situations of floods and especially on side roads. It is considered one type of structural bridge which has, among other characteristics, an easy transportation and assembly of the elements. The development is carried out, at this early stage of the project, only about the verification and sizing of structural elements of the superstructure of the bridge. For this purpose, it relies on computer programs, and fundamentally on PCFrame Visual Taco. The first allows you to model the structure and determine the efforts of calculating the elements, and the second one assists at the scaling and the verifications in accordance with the Brazilian technical standards for timber bridges. The wood used in the project comes from the tree Eucalyptus saligna, which is easy to acquaint and manipulate and comes from the region Vale do Paraíba. The bridge in this case of application should have the characteristics mentioned below: short execution time, simplicity of structure and an assembly of a relatively low cost

No Brasil há muitos casos de cidades que sofrem com enchentes. Muitas vezes destroem grande parte da estrutura da cidade, ilhando e isolando muitas famílias. Contar com medidas de emergência para estes casos e para casos similares é de extrema importância. Este trabalho propõe o desenvolvimento de um projeto de uma ponte de madeira que pode ser utilizada em situações emergenciais como ocorre em situações de enchentes e principalmente em estradas vicinais. Considera-se uma tipologia estrutural da ponte que possui, entre outras características, a de fácil transporte dos elementos e a montagem. O desenvolvimento realizado é, nesta etapa inicial do projeto, apenas das verificações e do dimensionamento dos elementos estruturais refrentes a superestrutura da ponte. Para este intento, vale-se de programas computacionais, fundamentalmente o PCFrame e o VISUAL TACO. O primeiro permite modelar a estrutura e determinar os esforços de cálculo nos elementos e segundo auxilia nas verificações e dimensionamento em conformidade com as normas técnicas brasileiras para pontes de madeira. A madeira utilizada no projeto é o Eucalipto Saligna de fácil aquisição e manipulação na região do Vale do Paraíba. A ponte neste caso de aplicação deve ter as características de possuir curto tempo de execução, simplicidade de montagem da estrutura e custo relativamente baixo
Keywords: Pontes de madeira; Pontes - Projetos e construção; Inundações; Bridges